Association between low body temperature on admission and in-hospital mortality according to body mass index categories of patients with sepsis. Issue 44 (4th November 2022) - Ito, Yuta; Kudo, Daisuke; Kushimoto, Shigeki
Abstract : Hypothermia has been shown to be associated with a high mortality rate among patients with sepsis. However, the relationship between hypothermia and body mass index (BMI) with respect to mortality remains to be elucidated. We conducted this study to assess the association between hypothermia and survival outcomes of patients with sepsis according to BMI categories. This secondary analysis of a prospective cohort study enrolled 1184 patients (aged ≥ 16 years) with sepsis hospitalized in 59 intensive care units in Japan. Patients were divided into 3 BMI categories (<18.5 [low], 18.5–24.9 [normal], >24.9 [high] kg/m 2 ) and 2 body temperature (36 °C and ≥ 36 °C) groups. The primary outcome was in-hospital mortality rate. Associations between hypothermia and BMI categories with respect to in-hospital mortality were evaluated using multivariate logistic regression analysis. Of the 1089 patients, 223, 612, and 254 had low, normal, and high BMI values, respectively. Patients with body temperature < 36 °C (hypothermia) had a higher in-hospital mortality rate than that had by those without hypothermia in the normal BMI group (25/63, 39.7% vs. 107/549, 19.5%); however, this was not true for patients in the low or high BMI groups. A significant interaction was observed between hypothermia and normal BMI for in-hospital mortality (odds ratio, 1.56; 95% confidence interval, 1.00–3.41; P value for interaction = .04); however, such an interaction was not found between hypothermia and low or high BMIs. Patients with sepsis and hypothermia in the normal BMI subgroup may have a higher mortality risk than that of those in the low or high BMI subgroups and, therefore, require more attention.